Acylamido-based anion-functionalized ionic liquids for efficient synthesis of poly(isosorbide carbonate). Issue 6 (10th December 2021) - Fang, Wenjuan; Xu, Fei; Zhang, Yaqin; Wang, Heng; Zhang, Zhencai; Yang, Zifeng; Wang, Weiwei; He, Hongyan; Luo, Yunjun
Abstract : A catalytic system containing an acylamido-based anion was developed for the synthesis of bio-based polycarbonate by efficient activation of monomers. Abstract : Using biomass and renewable feedstocks to prepare high value-added products instead of conventional petrochemicals has received extensive attention recently. In this work, a facile and phosgene-free approach for synthesizing bio-based polycarbonate is developed via melt polycondensation of isosorbide (ISB) and dimethyl carbonate (DMC), which are both derived from renewable biomass resources and CO2 . Several kinds of acylamido-based anion-functionalized ionic liquids (ILs) are prepared and used as catalysts to promote the reaction of ISB and DMC. Their catalytic performances in the transesterification stage and the polycondensation stage are evaluated. Results show that acylamido-based ILs with a low anion–cation interaction energy and a high natural population analysis atomic charges of the nitrogen atom exhibited good catalytic performance. Furthermore, by using tetrabutylphosphonium phthalimide as the catalyst, the selectivity of carboxymethylation of DMC and conversion of ISB significantly increased to 99.6% and 99.0%, respectively. Quantum chemical calculations reveal that the dramatic enhancement of endo -OH reactivity originated from the interactions between the acylamido and –OH groups. Based on the NMR data and DFT calculations, a plausible synergistic catalytic mechanism involving cation–anion is proposed. This work not only provides guidance for the design and synthesis of efficient IL catalysts, but also is applicable to exploring the industrial possibilities of developing value-added bioproducts from renewable feedstocks.